2017
DOI: 10.1016/j.trsl.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species as signaling molecules in the development of lung fibrosis

Abstract: Pulmonary fibrosis is a relatively rare but devastating disease characterized by the excessive deposition of extracellular matrix. The increased matrix results in reduced lung compliance and increased work of breathing, while the obliteration of alveolar-capillary structures can result in hypoxemia and pulmonary hypertension, which manifests clinically as worsening shortness of breath, respiratory failure and death. Unbiased genome wide association studies combined with animal models suggest that damage to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 67 publications
4
52
0
2
Order By: Relevance
“…Thus, direct reads of proteome content suggest that individual cell types may differentially respond to mitochondria need and/or management in response to the challenges of chronic aging and acute stress insults. These results are consistent with the emerging importance of complex I and III on global cellular health during aging and its response through metabolic cascades including the TCA cycle (6,(34)(35)(36)(37)39,43,64,65).…”
Section: Impact Of Mitochondria Energetics On Aging and Influenza Chasupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, direct reads of proteome content suggest that individual cell types may differentially respond to mitochondria need and/or management in response to the challenges of chronic aging and acute stress insults. These results are consistent with the emerging importance of complex I and III on global cellular health during aging and its response through metabolic cascades including the TCA cycle (6,(34)(35)(36)(37)39,43,64,65).…”
Section: Impact Of Mitochondria Energetics On Aging and Influenza Chasupporting
confidence: 82%
“…Specifically, in mitochondrial pathways and related mitochondrial stress responsive pathways (60)(61)(62)(63), changes that are now implicated in the aging process from multiple perspectives. In particular, both complex I and complex III and their links to key metabolic pathways are asserted to be drivers of the aging process (6,(34)(35)(36)(37)39,43,64,65). Herein, we noted substantial changes in the expression of mitochondrial proteins involved in both complexes, with a marked increase in abundance of mitochondrial components in AM cells compared to AT2 cells, suggestive of cell specific differential responses reflecting their unique roles in the pathobiology of the aging process and differential response to chronic particulate and pathogen environmental stresses such as viral/bacterial challenge leading to pneumonia in the elderly and long-term impact on recovery (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we summarize the most relevant research regarding the correlation between oxidative stress and EndMT, and their role in SSc-associated vascular damage and remodeling. Readers interested in a more comprehensive discussion concerning the mechanisms involved in the onset and progression of the fibrotic process can refer to other recent excellent reviews ( 27 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several scientists have identified new roles of redox homeostasis. It is suggested that ROS (e.g., H 2 O 2 ) at low levels serve as second messenger, and low MW thiols monitor the cellular redox state and play a decisive role in triggering physiological pathways like programmed cell death and DNA replication (Remacle et al, 1995;Gonzalez-Gonzalez et al, 2017;Lorenzen et al, 2017;Phull et al, 2018). Besides, thiol peroxidases appear to be important players in redox signaling processes.…”
Section: Redox-dependent Processesmentioning
confidence: 99%